Perancangan Sistem Informasi Absensi Pegawai Menggunakan Qr Code dan Linear Congruent Method Berbasis Web: Studi Kasus : SMP Perguruan Ira - Martha A Lumbantoruan; Niko Surya Atmaja; Rico Imanta Ginting (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
SMP Perguruan IRA is a private educational institution that still records employee attendance using attendance books. This method causes several problems, such as queues during attendance recording, difficulties in searching attendance data, and inefficiencies in generating attendance reports. This study aims to design a web-based employee attendance information system using QR Code and the Linear Congruential Method (LCM) to address these issues. QR Code technology enables employees to record attendance practically through smartphone scanning, while LCM is used to periodically regenerate QR Codes by producing pseudo-random values, thereby reducing the risk of code misuse through sharing or photography. The proposed application stores attendance data in a database, allowing fast data retrieval and automatic report generation. The results indicate that the web-based application provides a more efficient attendance recording process, faster data retrieval, and easier report management compared to the previous approach. Therefore, the integration of QR Code and LCM in a web-based application is considered effective in improving employee attendance management at SMP Perguruan IRA.